Diversity, habitats and conservation threats of syngnathid (Syngnathidae) fishes in Malaysia - Lim, A.C.O.; Chong, V.C.; Wong, C.S.; Choo, C.K. (2011)
This study comprehensively documents fish diversity of the family Syngnathidae in Malaysia and its adjacent waters. The results from the present study and records of syngnathids from museum collections and reviewed literature were collated. High species richness with a total of 50 species encompassing all subfamilies of the Syngnathidae, the Hippocampinae, Doryrhamphinae, Syngnathinae and Solegnathinae, were recorded from Malaysian waters. Two species Siokunichthys bentuviai Clark 1966 and Syngnathus pelagicus Linnaeus 1758 were previously not known to be distributed within the Malaysian region. Highest species richness was recorded from the Semporna Islands, Sabah. Habitats where syngnathids were recorded include marine macroalgal beds, coral reefs, coastal areas, estuaries, rivers and streams. Syngnathid fishes appear to be cryptic, live in low densities and display patchy distributions. The major threats to syngnathid conservation in Malaysia include overexploitation, by-catch, habitat destruction and degradation, recreational activities and pollution.